The Relationship between Public Communication of Tepuk Sakinah and Public Perception of Moral Messages - Suhendra Saputra Jaya; Aris Subagio (Universitas Nusa Cendana, 2026)
This study was conducted to examine and analyze public perception of the moral message contained in Tepuk Sakinah as a form of public communication created by the Office of Religious Affairs (KUA). This study aims to determine the relationship between public communication practices and public perception. This study used a quantitative correlational method involving 40 respondents selected through purposive sampling based on their level of familiarity with Tepuk Sakinah. Data were obtained through a structured questionnaire that had been distributed with measurements of public communication dimensions and perceptions of the ABC Attitude Model (cognitive, affective, and conative). Then, the results were analyzed using Spearman's rho correlation. The findings showed that Tepuk Sakinah was considered to have a positive influence on all dimensions. As a result, the cognitive aspect received the highest average score. These findings indicate that the public's understanding of moral values in family life is strong. The analysis also revealed a strong positive relationship between public communication and public perception (r = 0.753, p < 0.001). Meanwhile, the affective dimension had the strongest correlation, indicating that emotional involvement in shaping audience responses is paramount.